A 90-DAY SUBCHRONIC TOXICOLOGICAL ASSESSMENT of DEINOCOCCUS GRANDIS FERMENTED SOYMILK IN SPRAGUE-DAWLEY RATS - Jhou, Bo-yi; Jiang, Yih-min; Lin, Yi-chin; Tsai, Yueh-ting; Chen, Chin-chu (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Despite the fact that there was no adverse effect observed in previous animal safety studies of Deinococcus grandis (D. grandis) fermented soymilk, including acute oral toxicity assay, 3 different test systems of genotoxicity test and teratogenicity study, whether D. grandis fermented soymilk is safe for long-term use remains unknown. Therefore, the study was conducted further to clarify the edible safety of D. grandis fermented soymilk for long term use. Methods: Eighty Sprague-Dawley (SD) rats were divided into four groups, each consisting of ten male and ten female rats. Rats were orally administrated with reverse osmosis water (control) or 1,000, 2,000 and 3,000 mg/kg b.w./d freeze dried D. grandis fermented soymilk powder for 90 consecutive days. Clinical observation of the rats was carried out daily. The body weight and feed intake of the rats were recorded weekly. At the end of the study, all rats were sacrificed and the blood and organs were collected for hematology, clinical biochemistry and histopathological examination. Results: During the study period, no abnormality occurred in clinical signs, body weight, and ophthalmological examination. There were no significant differences in urinalysis, hematology and clinical biochemistry parameters between the treatment and control group. Necropsy and histopathological examination showed no treatment-related change. Conclusion: According to the results, the no-observed-adverse-effect level (NOAEL) of D. grandis fermented soymilk was greater than 3,000 mg/kg b.w./d in SD rats. Keywords: Deinococcus grandis (D. grandis), 90-day subchronic toxicity, NOAEL, Safety assessment, GKB-Aid 1995